Lexical Knowledge and the Achievement of Communicative Competence (Linguist, 2025)
The lexicon is one essential components in building, organizing, and developing the language. The weakness and limitations of the lexicon may lead to clear frustration in the cognitive communication and strategic competence for learners. In order to develop these lexical abilities along with another, it is assumed that the learner has to internalized previously  a sufficient and understandable amount of lexical units, coupled with their various and different meanings; because the lack of lexical knowledge becomes a factor inhibiting the development of many others cognitive competencies. We assume that this participation will contribute to raising some questions in this regard, to the extent that it will highlight some aspects of the shortcomings of teaching the lexicon in the traditional way, and the consequent shortcomings in the skill of reading, writing, speaking and listening, and we suggest instead some solutions to develop the teaching of the lexicon. This is based on the findings of modern cognitive linguistics theories in particular.
Keywords: lexis; lexical units; lexical competence; lexical knowledge; volume and depth of lexical knowledge; cognitive adequacy; strategic sufficiency